Where does CSR come from and where does it go? A review of the state of the art - Sara Rodriguez-Gomez; Maria Lourdes Arco-Castro; Maria Victoria Lopez-Perez; Lazaro Rodríguez-Ariza (Administrative Sciences, 2020)
It can be said that business ethics are integrated into companies through Corporate Social Responsibility (CSR), which cannot be defined in a single way, nor has its concept remained unchanged since its appearance in the business world. The contributions made in the field of research have been evolving towards models and theories that are more in line with principles that consider a plurality of stakeholders, from utilitarian or shareholder-centered approaches to others that are more integrative; the consideration of the demands and requirements of stakeholders, and the institutional drive through the establishment of regulatory frameworks aimed at providing conceptual frameworks of reference and indicators that make it possible to manage and make decisions taking into account the ethical dimension of problems or conflicts, are decisive. In this area, the objectives of sustainable development as part of Agenda 2030 are particularly relevant and are providing a boost to innovations aimed at improving the environment and the rational use of resources. This paper attempts to gather the main conceptual contributions on the situation and evolution of CSR, providing insights regarding future CSR studies, its objectives, and goals which, together with the interests and positions of the stakeholders from different perspectives, raises the possibility of analyzing CSR from different points of view, giving rise to different theories that try to serve as a framework for the study of CSR.
Keywords: 350; corporate social responsibility; innovation; stakeholders; sustainability